Innovative mobile and internet services in ubiquitous computing : proceedings of the 11th international conference on innovative mobile and internet services in ubiquitous computing (IMIS-2017) /: proceedings of the 11th international conference on innovative mobile and internet services in ubiquitous computing (IMIS-2017). ([2018]) - Unknown
No abstract available